PENYIMPANAN DAN PEMBUANGAN OBAT PADA MASYARAKAT SERTA ESTIMASI NILAI EKONOMI OBAT YANG TIDAK DIGUNAKAN (NARRATIVE REVIEW) - Dismayana Anggita Rosti; Sri Wahyuningsih (LPPM Universitas Bina Bangsa, 2023)
There are still many people in everyday life who do not know how to store and dispose of drugs properly. Some drugs that are stored at home, are not stored properly and many are keep for a long time so that the drugs are damaged or accumulate until they expire, and are disposed of carelessly. This results in waste of health costs, drug waste can pollute the environment and endanger humans. This study was conducted to identify how people store and dispose of drugs at home as well as estimate the economic value of drugs that are not used. The method is in the form of a narrative review using the results of journal articles that have been published through electronic media in 2013-2023. Article searches are carried out by hand searching on three databases, namely Pubmed, Science Direct and Google Scholar. The results of the study show that the majority of people keep drugs at home, drugs that are thrown away by the average person throw them in the trash, and estimated of the economic value of drugs that are no longer used in various regions have a high value, causing a loss of economic value